Purification and characterization of enantioselective N-acetyl-β-Phe acylases from Burkholderia sp. AJ110349. Issue 1 (2nd January 2016) - Imabayashi, Yuki; Suzuki, Shun'ichi; Kawasaki, Hisashi; Nakamatsu, Tsuyoshi
Abstract: For the production of enantiopure β-amino acids, enantioselective resolution of N -acyl β-amino acids using acylases, especially those recognizing N -acetyl-β-amino acids, is one of the most attractive methods. Burkholderia sp. AJ110349 had been reported to exhibit either ( R )- or ( S )-enantiomer selective N -acetyl-β-Phe amidohydrolyzing activity, and in this study, both ( R )- and ( S )-enantioselective N -acetyl-β-Phe acylases were purified to be electrophoretically pure and determined the sequences, respectively. They were quite different in terms of enantioselectivities and in their amino acids sequences and molecular weights. Although both the purified acylases were confirmed to catalyze N -acetyl hydrolyzing activities, neither of them show sequence similarities to the N -acetyl-α-amino acid acylases reported thus far. Both ( R )- and ( S )-enantioselective N -acetyl-β-Phe acylase were expressed in Escherichia coli . Using these recombinant strains, enantiomerically pure ( R )-β-Phe (>99% ee) and ( S )-β-Phe (>99% ee) were obtained from the racemic substrate. Graphical abstract: : Enantioselectivity of purified acylases. N -Ac-( R, S )-β-Phe was incubated with either purified N -Ac-( R )- or ( S )-β-Phe acylase. The reaction products were analyzed by HPLC.